Indonesia Pengaruh Edukasi Terstruktur Berbasis Booklet Terhadap Kepatuhan, Kualitas Hidup, Dan Kadar Glukosa Darah Sewaktu Pasien Diabetes Melitus Tipe 2 Di Puskesmas Kota Tasikmalaya, Jawa Barat, Indonesia - Listya Permatasari; Tri Murti Andayani; Fita Rahmawati (Journal of Pharmaceutical and Sciences, 2026)
This study aimed to analyze the effect of structured booklet-based education on medication adherence, quality of life, and random blood glucose levels in patients with type 2 diabetes mellitus at primary health care centers in Tasikmalaya City. This research employed a quasi-experimental design with a pretest–posttest control group approach. A total of 72 respondents were divided into an intervention group (n=36) and a control group (n=36). Medication adherence was assessed using the Morisky Green Levine Scale (MGLS), quality of life was measured using the Diabetes Quality of Life–Brief Clinical Inventory (DQoL-BCI), and clinical outcomes were evaluated using random blood glucose levels. The results showed that the intervention group experienced a significant improvement in medication adherence (p<0.001) and a significant reduction in random blood glucose levels (p<0.001). Quality of life also improved significantly within the intervention group (p<0.001); however, the difference in posttest quality of life between groups was not statistically significant (p=0.317). The improvement in quality of life observed in both groups may have been influenced by routine primary health care services, repeated attention during the study (Hawthorne effect), as well as support from health cadres or the surrounding environment that was not specifically measured. ANCOVA analysis demonstrated that after controlling for confounding variables, structured booklet-based education had a significant effect on medication adherence (p<0.001) and random blood glucose levels (p=0.048), but not on quality of life (p=0.055). In conclusion, structured booklet-based education was effective in improving medication adherence and reducing random blood glucose levels, but it did not show a statistically significant effect on quality of life in patients with type 2 diabetes mellitus.